2022
DOI: 10.1021/acsami.1c18110
|View full text |Cite
|
Sign up to set email alerts
|

Toward Enhanced Electrochemical Performance by Investigation of the Electrochemical Reconstruction Mechanism in Co2V2O7 Hexagonal Nanosheets for Hybrid Supercapacitors

Abstract: As for hybrid supercapacitors, it is important to enhance the long cycling performance and high specific capacitance. In this paper, cobalt vanadate (Co 2 V 2 O 7 ) hexagonal nanosheets on nickel foam are manufactured by a facile hydrothermal method and then transformed into numerous smaller size interconnected hierarchical nanosheets without any shape change via electrochemical reconstruction. Benefiting from the favorable architecture of hierarchical nanosheets via electrochemical reconstruction, the Co 2 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Also, Hosseini et al [ 56 ] fabricated Co 3 V 2 O 8 ‐Ni 3 V 2 O 8 TLs@PCNFs//PCNFs reported SE of 59.7 Wh kg −1 at 1970 W kg −1 . Similar to the present work, the aqueous hybrid supercapacitor device based on Co 2 V 2 O 7 //rGO was fabricated by Wang et al, [ 11 ] which attained 35.2 Wh kg −1 SE at 101 W kg −1 SP. Moreover, the SHSD and ASHD devices manufactured in the present work demonstrated higher performance than the reported only similar device by Wang et al [ 11 ] in terms of SE and SP.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Also, Hosseini et al [ 56 ] fabricated Co 3 V 2 O 8 ‐Ni 3 V 2 O 8 TLs@PCNFs//PCNFs reported SE of 59.7 Wh kg −1 at 1970 W kg −1 . Similar to the present work, the aqueous hybrid supercapacitor device based on Co 2 V 2 O 7 //rGO was fabricated by Wang et al, [ 11 ] which attained 35.2 Wh kg −1 SE at 101 W kg −1 SP. Moreover, the SHSD and ASHD devices manufactured in the present work demonstrated higher performance than the reported only similar device by Wang et al [ 11 ] in terms of SE and SP.…”
Section: Resultsmentioning
confidence: 60%
“…Similar to the present work, the aqueous hybrid supercapacitor device based on Co 2 V 2 O 7 //rGO was fabricated by Wang et al, [ 11 ] which attained 35.2 Wh kg −1 SE at 101 W kg −1 SP. Moreover, the SHSD and ASHD devices manufactured in the present work demonstrated higher performance than the reported only similar device by Wang et al [ 11 ] in terms of SE and SP. However, the reported energy densities for Co 3 V 2 O 8 //AC, [ 49 ] Co 3 V 2 O 8 //AC, [ 50 ] and Co 3 V 2 O 8 ‐Ni 3 V 2 O 8 ‐PCNFs//PCNFs [ 56 ] HASDs are slightly higher than the present work due to the use of Ni‐foam (NF) as a conductive substrate since Ni foam can add its self‐capacitance in the alkaline device.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…We found that soaking the electrodes in the electrolyte for a long time (after activation) was quite favorable for enhanced cycling stability. Such drastic enhancement in electrochemical performance is associated with the electrochemical reconstruction of the electrode materials during cycling and soaking the electrode in electrolyte solution for a long time [ 32 ]. It is important to note that, after the soaking process, the capacitance retention increased to 207% at the 38,000th cycle, which can be associated with the re-activation of the electrode.…”
Section: Resultsmentioning
confidence: 99%